The ant genus Stenamma Westwood (Hymenoptera: Formicidae) redefined, with a description of a new genus Propodilobus - Branstetter, Michael G. (Zootaxa, 2009)
The myrmicine ant genus Stenamma Westwood is redefined and a new diagnosis of the worker caste is presented. Justified by both morphology and molecular data, two species are removed from Stenamma and transferred to the genus Lordomyrma Emery: L. bhutanensis (Baroni Urbani) comb. n. and L. sinensis (Ma, Xu, Makio & DuBois) comb. n. Based on compelling differences in morphology, a third species originally described in Stenamma is transferred to the genus Propodilobus gen. n.: P. pingorum (DuBois) comb. n. Molecular results also indicate that Stenamma, as newly defined here, is a monophyletic genus that forms a clade with Aphaenogaster Mayr and Messor Forel. Additional notes on the diversity and distributions of Stenamma, Lordomyrma, and Propodilobus are provided.